2004
DOI: 10.1016/j.ejcts.2004.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative outcome and long-term survival of surgery for acute post-infarction mitral regurgitation

Abstract: In patients with acute post-infarction mitral regurgitation, perioperative mortality is high, but can be improved with concomitant CABG in addition to valve surgery. Long-term outcome of survivors is favourable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 18 publications
2
54
0
5
Order By: Relevance
“…4,9,10 However, the diagnosis of PMR is not always easy because patients are often elderly and frequently diagnosed with a particularly severe clinical presentation, all factors associated with high operative mortality. 2,11 Thus, surgical treatment, although recommended by guidelines, 12 is often considered too risky, 4 and a large proportion of patients with acute MR after MI may not be offered surgery. 4 However, recent reports have demonstrated that for surgery of MR in general, a marked reduction in operative mortality has been observed lately, 13 particularly in elderly patients.…”
mentioning
confidence: 99%
“…4,9,10 However, the diagnosis of PMR is not always easy because patients are often elderly and frequently diagnosed with a particularly severe clinical presentation, all factors associated with high operative mortality. 2,11 Thus, surgical treatment, although recommended by guidelines, 12 is often considered too risky, 4 and a large proportion of patients with acute MR after MI may not be offered surgery. 4 However, recent reports have demonstrated that for surgery of MR in general, a marked reduction in operative mortality has been observed lately, 13 particularly in elderly patients.…”
mentioning
confidence: 99%
“…Mortality of 16% to 24% has been reported. 3,6,11) Papillary muscle rupture typically occurs within the first week of an acute myocardial infarction. Rupture of the posteromedial papillary muscle is five to ten times more frequent than that of the anterolateral papillary muscle.…”
Section: Discussionmentioning
confidence: 99%
“…3,6,11) However, it is sometimes possible to repair the mitral valve by re-attaching the disrupted papillary muscle head. In this case, the area of prolapse was too broad to be repaired.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…A revascularização cirúrgica do miocárdio deve ser sempre considerada na presença de complicações mecânicas do infarto, como ruptura de parede livre, comunicação interventricular 344 e ruptura ou disfunção de músculo papilar com grave repercussão hemodinâmica 345 , embora a cirurgia continue a ser realizada com elevado risco de mortalidade 345,346 . Nessas situações, o tratamento cirúrgico da complicação mecânica, associado ou não à revascularização do miocárdio, deve ser sempre indicado e desencadeado com urgência.…”
Section: -Revascularização Associada Ao Tratamento Das Complicações Munclassified